Response of Tomato Varieties and Organic Mulch on Growth and Products of Tomato (Lycopersicum esculentum Mill) - Dewi Yana; Ani Rahima (Postgraduate, University of Mataram, 2023)
Tomato plants are one of the most important vegetables after potatoes, eggplants, and chilies. Tomatoes can be eaten raw, they are also used as a flavoring ingredient in dishes, vegetables or made into soy sauce and sauces. the need for tomato plants is increasing every year. which type of organic mulch and variety is more appropriate for the growth of tomato plants, and how does the response of the three varieties of tomato plants to the type of organic mulch in increasing the growth and yield of tomato plants? Based on the description above, this study aimed to determine the best variety and type of organic mulch suitable for maximum growth and yield of tomato plants, as well as whether there was interaction between the two factors studied. This study used a 3 x 3 factorial Randomized Block Design (RBD) with 3 replications, so there were 27 experimental combinations. There are two factors studied, namely the variety factor (V) and the organic mulch factor (M). The results of this study that the variety of tomatoes has a very significant effect on Plant height (cm), Diameter of stem base (cm), Number of fruits per plant (fruit), Fruit weight per plant (g), Tomato fruit diameter (cm), Fruit weight (g). Organic mulch had no significant effect on Plant height (cm), Diameter of stem base (cm), Number of fruits per plant (fruit), Fruit weight per plant (g), Tomato fruit diameter (cm), and Fruit weight (g). The responses of the three tomato varieties were not significantly different to changes in the type of organic mulch in increasing the growth and yield of tomato plants.